Faces of poverty - Berrick, Jill Duerr (Oxford University Press, 1995)
Most Americans are insulated from the poor; it's hard to imagine the challenges of poverty, the daily fears of crime and victimization, the frustration of not being able to provide for a child. Instead, we are often exposed to the rhetoric and hyperbole about the excesses of the American welfare system. These messages color our perception of the welfare problem in the United States and they close the American mind to a full understanding of the complexity of family poverty. But who are these poor families? What do we know about how they arrived in such desperate straits? Is poverty their fate for a lifetime or for only a brief period? In Faces of Poverty, Jill Duerr Berrick answers these questions as she dispels the misconceptions and myths about welfare and the welfare population that have clouded the true picture of poverty in America